Quantum Dots in Glasses: Size‐Dependent Stokes Shift by Lead Chalcogenide. (6th August 2015) - Han, Na; Liu, Chao; Zhao, Zhiyong; Zhang, Jihong; Xie, Jun; Han, Jianjun; Zhao, Xiujian; Jiang, Yang
Abstract : Size‐dependent Stokes shift of PbS quantum dots (QDs) formed in the glasses was investigated. PbS QDs with diameters of 3.5 nm to 13.3 nm were precipitated in silicate glasses with different S/Pb ratios using the conventional thermal treatment method. Absorption and photoluminescence (PL) of PbS QDs were tuned from 0.9 μm (1.38 eV) to 2.3 μm (0.54 eV) by adjusting the diameters of PbS QDs from 3.5 nm to 13.3 nm. PL energies of QDs exhibited linear dependence on the absorption energies with a slope of 0.484 for PbS QDs with band gap energies larger than 0.98 eV, and the maximum Stokes shift was found to be 206.2 meV for 3.5 nm‐sized PbS QDs. For large PbS QDs with band gap energies smaller than 0.98 eV, Stokes shift was found to be 20 meV or smaller. The size‐dependent Stokes shift indicated that surface defects made the main contribution and relative energy positions of these surface defects were strongly dependent on the size of PbS QDs.